2016
DOI: 10.1515/pac-2016-0407
|View full text |Cite
|
Sign up to set email alerts
|

Arylxanthones and arylacridones: a synthetic overview

Abstract: Arylxanthones and arylacridones although not yet found in nature are becoming an important group of heterocyclic compounds due to their promising biological activities. Their central cores, xanthone and acridone, are recognized as interesting motifs for drug development mainly to be used in antitumour chemotherapy. The synthesis of this type of compounds is still scarce but several successful examples were recently published and a large variety of arylated xanthone and acridone derivatives were prepared. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…From all the xanthone-type compounds 163e170 isolated from the twigs of Maclura fruticosa, none of them exhibited inhibitory activity against a-glucosidase, at the tested experimental conditions (Table 6) [24]. Apart from the derivative 179 (IC 50 ¼ 72.2 mM), all xanthones were better inhibitors, with IC 50 ranging from 1.7 to 30.7 mM, than the positive control deoxynojirimycin (IC 50 ¼ 39.5 mM).…”
Section: Tablementioning
confidence: 97%
“…From all the xanthone-type compounds 163e170 isolated from the twigs of Maclura fruticosa, none of them exhibited inhibitory activity against a-glucosidase, at the tested experimental conditions (Table 6) [24]. Apart from the derivative 179 (IC 50 ¼ 72.2 mM), all xanthones were better inhibitors, with IC 50 ranging from 1.7 to 30.7 mM, than the positive control deoxynojirimycin (IC 50 ¼ 39.5 mM).…”
Section: Tablementioning
confidence: 97%
“…The first methods for the synthesis of xanthones were introduced by Michael and Kostanecki in 1883-1891 81,82 and in the 20 th century and until 2012 several extensive reviews have reported the state of the art regarding the synthesis of xanthones. 9,10,83,84 More recently reviews have focused on the synthesis of a very specific class of derivatives like carboxyxanthones, 85 hydroxanthones, 86 arylxanthones, 87 and thioxanthones 88 and, although azaxanthones have demonstrated therapeutic potential and interest as sensitizing chromophores, [89][90][91][92][93][94] their reports in medicinal chemistry are still sparse in the literature. Therefore, in this review, the recent exploitation of both scaffolds was considered from a medicinal chemistry point of view, with advanced synthetic methodologies applied for obtaining bioactive derivatives being displayed in the sections below.…”
Section: Introductionmentioning
confidence: 99%
“…14 Because of the wide spectrum of medicinal activity chemists have attempted to synthesize acridine derivatives by several ways that have been discussed in the reported review and multi-step synthetic routes under different reaction conditions and use of various reagents by conventional and non-conventional as well. 15 Some multicomponent methodologies have also been reported, like protic pyridinium ionic liquid, 16 L-proline, 17 nano ferrite 18 , etc. However, aspects of green chemistry need some more effort that could develop sustainable protocols.…”
Section: Introductionmentioning
confidence: 99%